A new model for analyzing hydraulic fracture initiation in perforation tunnels - Fallahzadeh, Seyed Hassan; Shadizadeh, S. (Taylor & Francis, 2013)
Hydraulic fracturing has been used for many years in order to stimulate the oil and gas wells for improving reservoir production. The challenge of fracture initiation pressure and near-wellbore fracture propagation is a complex problem especially in deviated and cased perforated holes. Understanding the stress distribution around the perforations is the key for analyzing the fracture initiation mechanism and thereby realizing the near-wellbore fracture geometry. In this article, a generic model is developed for estimating the initiation pressure as well as the orientation geometry of the fracture in the perforations around the borehole. The results of this study show that at any specific stress regime around the wellbore, there is an optimum perforation orientation that leads to lower fracture initiation pressure. © Taylor & Francis Group, LLC.